2014
DOI: 10.2147/ijn.s72659
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and stemness preservation of human adipose-derived stem cells by surface-modified in situ TiO2 nanofibrous surfaces

Abstract: Two important criteria of an ideal biomaterial in the field of stem cells research are to regulate the cell proliferation without the loss of its pluripotency and to direct the differentiation into a specific cell lineage when desired. The present study describes the influence of TiO 2 nanofibrous surface structures on the regulation of proliferation and stemness preservation of adipose-derived stem cells (ADSCs). TiO 2 nanofiber arrays were produced in situ onto T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, in the current study we show that stimulation of ASC with only TGF-β1 increases the expression of α-SMA, SM22α and calponin and that the resulting SMC are contractile too. It has been shown that culture substrates can influence cell function and differentiation capacity [33][34][35][36][37][38]. However, ASC cultured on TCPS, glass and PTMC all differentiated towards SMC after one week of stimula- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study we show that stimulation of ASC with only TGF-β1 increases the expression of α-SMA, SM22α and calponin and that the resulting SMC are contractile too. It has been shown that culture substrates can influence cell function and differentiation capacity [33][34][35][36][37][38]. However, ASC cultured on TCPS, glass and PTMC all differentiated towards SMC after one week of stimula- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…The modified fibres supported MG-63 osteoblast proliferation, penetration and ECM deposition [59]. Titanium dioxide (TiO2) nanofibrous scaffolds demonstrated better cell adhesion and proliferation compared to the flat control surfaces using cell cycle analysis [60]. Expression of stemness markers genes including Nanog3, Rex-1, SOX-2 and nestin of the ADSCs cultured on the control and TiO2 nanofibrous surfaces was also higher on the fibrous surfaces than controls surfaces [60].…”
Section: Nanofibres In Bone Tissue Engineeringmentioning
confidence: 99%
“…To support tissue formation, it has been extensively popular to load nanofibres with bioactive factors to modify the cell environment and mimic the natural ECM niche. Biofactors can be loaded onto nanofibres using several techniques including blending, coaxial spinning and immobilization [60][61][62][63]. Blending of the desired factors during electrospining can lead to aggregation homogenous dispersion along the fibres [60][61][62][63].…”
Section: Nanofibres In Bone Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations